Santa Teresa de Jesus e seu influxo na espiritualidade laical = Saint Teresa of Jesus and the influx of secular spirituality - Carli, Vitoria Andreatta De (Teocomunicação, 2022)
The article presents the figure of Saint Theresa as inspiration for the experience of an authentic Christian spirituality in its lay modality. In times of disbelief in the present post-pandemic context, of war and faced with the current "God’s crisis of believers" (RATZINGER, 2015), one can perceive the reality of many in living on the margins of God and the Church or even experiencing false forms of Christian spirituality. Despite the distance between Theresa’s time and ours, this saint contemplates us with her witness that is "incomparable in contemplation and indefatigable in action" (PAULO VI, 1970a). She achieved this feat with all the weapons at her disposal, especially prayer as a gift of her relationship with God and her commitment to the world in an integrated and luminous way. Resorting to her heritage today has much to suggest and reveal for the experience of the authentic Christian spirituality. It is also an invitation to the lay faithful to recover the intensity of faith and the intensity of the life of prayer. In other words, to put all of life daily before God to exercise the relationship with Him, thus uniting being and mission; word and life as the mystic did. Considering this, he concludes that Teresa’s model is relevant above all in the aspects of her doctrine regarding the life of prayer; of unity between faith and life and that there is no Christian life without a struggle. The proposed method will be essentially bibliographic-analytic to understand the deep friendship of Theresa with God and from there the need to communicate her experience to those who approached her., , O artigo apresenta a figura de Santa Teresa como inspiração para a vivência de uma autêntica espiritualidade cristã em sua modalidade laical. Em tempo de descrença no atual contexto pós-pandêmico, de guerra e diante da atual "crise de Deus dos crentes" (RATZINGER, 2015), percebe-se a realidade de muitos em viver a margem de Deus e da Igreja ou ainda de experimentarem falsas formas de espiritualidade cristã. Apesar do distanciamento do tempo de Teresa do nosso, essa santa nos contempla com seu testemunho que é "incomparável na contemplação e infatigável na ação" (PAULO IV, 1970a). Logrou tal feito com todas as armas ao seu alcance, em especial a oração como dom de sua relação com Deus e o compromisso com o mundo de forma integrada e luminosa. Recorrer hoje à sua herança tem muito a sugerir e revelar para a vivência da autêntica espiritualidade cristã. É um convite também aos fiéis leigos para recuperar a intensidade da fé e a intensidade da vida de oração. Em outras palavras, colocar toda a vida cotidianamente diante de Deus para exercitar a relação com Ele, unindo assim o ser e missão; palavra e vida como fez a mística. Considerando isso, conclui que o modelo de Teresa é atual sobretudo nos aspectos de sua doutrina a respeito da vida de oração; da unidade entre fé e vida e que não há vida cristã sem luta. O método proposto será essencialmente bibliográfico-analítico para depreender a profunda amizade de Santa Teresa com Deus e desde aí a necessidade em comunicar sua experiência aos que dela se acercavam.